2006
DOI: 10.1523/jneurosci.2897-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin2-Mediated Internalization of Mammalian Odorant Receptors

Abstract: ␤-arrestin2 with high affinity and are internalized via a clathrin-dependent mechanism. After prolonged odorant exposure, receptors are not targeted to lysosomal degradation but accumulate in recycling endosomes. Odorant-induced odorant receptor desensitization is promoted by cAMPdependent protein kinase A phosphorylation and is dependent on serine and threonine residues within the third intracellular loop of the receptor. Moreover, ␤-arrestin2 is redistributed into the dendritic knobs of mouse olfactory recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 52 publications
1
80
0
Order By: Relevance
“…The phosphorylation of GPCR is followed by the recruitment of b-arrestins and internalization of GPCRs. A recent study has shown that olfactory receptors can also be inactivated by this mechanism (Mashukova et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The phosphorylation of GPCR is followed by the recruitment of b-arrestins and internalization of GPCRs. A recent study has shown that olfactory receptors can also be inactivated by this mechanism (Mashukova et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…In mice, it has been shown that odorant receptors are internalized via clathrin-dependent endocytosis (Mashukova et al, 2006). The authors of that study also showed that prolonged odorant exposure led to the accumulation of receptors in recycling endosomes, and not to lysosomal degradation.…”
Section: Endocytosismentioning
confidence: 96%
“…Like other G-proteincoupled receptors (GPCRs) (Ferguson, 2001;Seachrist and Ferguson, 2003;von Zastrow, 2001), odorant receptors appear to be internalized upon activation via a clathrin-dependent process, as indicated by studies in channel catfish (Rankin et al, 1999) and mouse (Mashukova et al, 2006). After prolonged odorant exposure, receptors are not targeted to lysosomal degradation but accumulate in recycling endosomes, and adaptation of olfactory receptor neurons to odorants can be abolished by the inhibition of clathrin-mediated endocytosis (Mashukova et al, 2006). It is not clear to what extent the endocytosis observed in these experiments may be ligand specific.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to 62 ORs, we also identified factors enhancing OR expression at the surface (REEP1, RPT1, and RTP2) (77,78) and different subunits of PKA attenuating OR activity by phosphorylation (79).…”
Section: Toward the Delineation Of The Ciliary Membrane Proteomementioning
confidence: 99%